N6-methyladenosine modification of viral RNA and its role during the recognition process of RIG-I-like receptors - Li, Huanan; Guo, Yang; Qi, Wenbao; Liao, Ming (Frontiers in Immunology, 2022)
N6‐methyladenosine (m6A) is the most abundant RNA chemical modification in eukaryotes and is also found in the RNAs of many viruses. In recent years, m6A RNA modification has been reported to have a role not only in the replication of numerous viruses but also in the innate immune escape process. In this review, we describe the viruses that contain m6A in their genomes or messenger RNAs (mRNAs), and summarize the effects of m6A on the replication of different viruses. We also discuss how m6A modification helps viral RNAs escape recognition by exogenous RNA sensors, such as retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), during viral invasion. Overall, the goal of our review is to summarize how m6A regulates viral replication and facilitates innate immune escape. Furthermore, we elaborate on the potential of m6A as a novel antiviral target.